Kisspeptin Modulates Luteinizing Hormone Release and Ovarian Follicular Dynamics in Pre-pubertal and Adult Murrah Buffaloes - Pottapenjera, Vishalkumar; Rajanala, Srinivasa R.; Reddy, Chandrasekhar; Gangineni, Arunakumari; Avula, Kiran; Bejjanki, Sandeep K.; Sathagopam, Sriravali; Kesharwani, Surabhi; Velmurugan, Sathya (Frontiers in Veterinary Science, 2018)
Kisspeptin is a neuropeptide that governs the reproductive axis upstream to GnRH. We wanted to study whether kisspeptin modulates plasma LH and FSH levels and ovarian follicular dynamics in buffaloes and whether kisspeptin can be used for oestrus synchronizationfixed time artificial insemination (FTAI). We carried out these studies in comparison with buserelin, a potent GnRH agonist. Kisspeptin dose-dependently increased plasma LH levels. However, the kisspeptin-induced increase in LH was short-lived as the peak reached in 15-30 min returned to basal values by 1-2 h. The kisspeptin-induced increase in LH level was less compared to buserelin-induced increase in LH level which sustained over time. Kisspeptin did not enhance FSH release while buserelin resulted in a gradual increase over time. LH response to repeated injections of kisspeptin was more greater than that induced by buserelin. While buserelin inducedcreased an increase in the number of follicles, kisspeptin induced an increased in the growth rate of the follicle. In adult cycling animals, while both the drugs increased plasma LH levels, the increase was more greater in buserelin group compared to kisspeptin group. In contrast to the findings in pre-pubertal animals, kisspeptin induced an increased in both the number as well as the size of follicles compared to buserelin. Our studies on oestrus synchronization, using either kisspeptin-PGF2α-kisspeptin protocol or buserelin-PGF2α-buserelin Ovsynch protocol on day 0, 7 and 9, respectively, revealed that kisspeptin increased the number of follicles at wave emergence and the diameter of dominant follicle after 2nd dose of drug, the oestrus response rate and duration of oestrus, compared to buserelin. However, conception rate was not significantly different among the groups. From our studies, it appears that Kp and Buserelin differentially modulate follicular dynamics depending on the reproductive age of the animals.However, studies in a larger herd are required to confirm whether kisspeptin can be used for oestrous synchronization in buffaloes.